2017
DOI: 10.1002/cssc.201601356
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Research into the Reduction Mechanism for the Solvent/Additive in a Sodium‐Ion Battery

Abstract: The solid-electrolyte interface (SEI) film in a sodium-ion battery is closely related to capacity fading and cycling stability of the battery. However, there are few studies on the SEI film of sodium-ion batteries and the mechanism of SEI film formation is unclear. The mechanism for the reduction of ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC), ethylene sulfite (ES), 1,3-propylene sulfite (PS), and fluorinated ethylene carbonate (FEC) is studied by DFT. The reaction activation ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 43 publications
5
52
0
Order By: Relevance
“…Meanwhile, in the first two cases, namely intercalation and pseudocapacitance mechanisms, the large irreversible capacity observed below 0.3 V during the first discharge cycle in the galvanostatic cycling curves is ascribed to the formation of an SEI layer with no further explanation; notwithstanding that, XPS analysis is used to corroborate C-coating formation in the anatase TiO 2 nanorods tested in the intercalation studies. In the XPS study, [188] besides the determination of the SEI composition in agreement with DFT work by Q. Liu et al, [282] including the formation of NaF during cycling, the degradation of the PVDF binder during slurry preparation was detected when measuring the presence of NaF in the pristine electrodes: this extent was further confirmed by means of 19 F magic angle spinning NMR. In this regard, some efforts have been dedicated to find a correlation between the SEI and the surface area of nanoporous carbon-TiO 2 composites [289] ; in fact, it has been shown that SEI layer formation increases on the anode having larger surface area.…”
Section: Sei Of Ti-based Oxidessupporting
confidence: 81%
See 1 more Smart Citation
“…Meanwhile, in the first two cases, namely intercalation and pseudocapacitance mechanisms, the large irreversible capacity observed below 0.3 V during the first discharge cycle in the galvanostatic cycling curves is ascribed to the formation of an SEI layer with no further explanation; notwithstanding that, XPS analysis is used to corroborate C-coating formation in the anatase TiO 2 nanorods tested in the intercalation studies. In the XPS study, [188] besides the determination of the SEI composition in agreement with DFT work by Q. Liu et al, [282] including the formation of NaF during cycling, the degradation of the PVDF binder during slurry preparation was detected when measuring the presence of NaF in the pristine electrodes: this extent was further confirmed by means of 19 F magic angle spinning NMR. In this regard, some efforts have been dedicated to find a correlation between the SEI and the surface area of nanoporous carbon-TiO 2 composites [289] ; in fact, it has been shown that SEI layer formation increases on the anode having larger surface area.…”
Section: Sei Of Ti-based Oxidessupporting
confidence: 81%
“…Energy Mater. [282] Although this study does not account for electrode effects, it has evaluated the decomposition mechanism of EC, PC, and VC. Diagram of the Auger electron emission process for a model atom.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…In the gas phase, intermediates 12 and 13 can be generated from intermediate 18, where the excess electron goes to Li rather than S and the transition state was also located with an imaginary frequency of 500 cm À1 . However, similar to the report from Liu et al for Na + (ES), 47 in solution as the electron partially transfers from Li to S, the much stronger solvation of Li s+ than that of neutral Li can signicantly decrease the energy of the compound. Thus, the transition state for the S-O bond cleavage does not exist in solution and the path from 18 to intermediates 12 and 13 may not be plausible.…”
Section: Models and Computational Detailssupporting
confidence: 79%
“…A very important practical property which, however, needs specific simulations and where more or less all SIBs still are struggling, is the ability to create a stable solid electrolyte interphase (SEI), and this is most often made by reducing solvents or additives to SEI forming compounds. Liu et al used DFT to study the changes in energies, enthalpies, and free energies for all steps in a number of possible reduction reaction of common carbonate solvents: ethylene carbonate (EC), propylene carbonate (PC), and vinylene carbonate (VC)—the latter the most common additive since a long time for LIB electrolytes—with Na + present. EC was found to undergo a one‐electron decomposition (Δ G = −874.7 kJ mol −1 ) forming (CH 2 CH 2 CO 3 Na) 2 , PC similarly reduced to (CH 2 CH 2 CH 2 CO 3 Na) 2 (Δ G = −970.4 kJ mol −1 ), and finally VC creating (CHCHCO 3 Na) 2 (Δ G = −974.8 kJ mol −1 ).…”
Section: Liquid Electrolytesmentioning
confidence: 99%